Adenolymphoma (Warthin's tumor) with multiple sarcoid-like granulomas - Ryska, A; Seifert, G (Pathology, research and practice, 1999)
Five cases of adenolymphoma (Warthin's tumor) (AL) with numerous sarcoid-like granulomas within the lymphoid stroma are described. All patients were males, aged from 44 to 71 years (mean 57.3 years); all tumors were localized in the parotid gland. Fine needle aspiration cytology was performed in two cases 7.5 and 2 weeks before operation, respectively. Microscopic examination demonstrated the typical structure of AL. In addition, dispersed throughout the lymphoid stroma there were numerous granulomas formed by both epithelioid and multinucleated giant cells of Langhans type, strongly resembling sarcoidosis. The pathogenesis of the granulomatous change remains speculative. It could be caused by a toxic effect of the cysts' contents but probably not by its direct action; the spread of the fluid via sinuses into the lymphatic tissue seems to be more probable. We presume that the previous FNA may have some triggering effect. Granulomatous transformation of the lymphoid stroma resembling sarcoidosis is rare, but should be included in the spectrum of secondary changes in AL. It is not limited to metaplastic AL; it can be seen in an otherwise typical AL without any additional histologic changes. Knowledge of a previous FNA and awareness of the possibility of this peculiar histologic change are necessary to avoid incorrect diagnosis.
Keywords: senioři; jehlová biopsie; Immunoenzyme Techniques; adenolymfom; Adenolymphoma; Sarcoidosis; buňky stromatu; Biopsy, Needle; Granuloma; Middle Aged; mužské pohlaví; Adult; Follow-Up Studies; Biomarkers, Tumor; následné studie; imunoenzymatické techniky; Parotid Neoplasms; nádorové biomarkery; granulom; Humans; sarkoidóza; nádory příušní žlázy; lidé středního věku; Stromal Cells; dospělí; Aged; lidé; Male